THEOLOGICAL AND POLEMICAL RECEPTION ON WESTERN SCHOLARSHIP IN AL-QUR’ĀN AND TAFSĪR STUDIES IN INDONESIA - Yusuf Rahman (Jurnal Ushuluddin, 2019)
This study aims to examine responses and receptions of Indonesian Muslim scholars on Western non-Muslims scholarship in the study of al-Qur’ān and tafsīr. Generally, the reception of their works can be divided into two responses: positive and negative. Yet, this study focuses on negative responses. The findings indicate that the responses are theological and polemical. The main sources of this study are works - printed and online - written by the opponents of Western scholarship in Indonesia. These works are analyzed chronologically to see the reasons behind their rejection. This study shows that Indonesian Muslim scholars responded negatively to Western scholarship on Qur’ānic studies because Western scholars have a hidden agenda in their works. This attitude, the article argues, is very polemical because it essentially generalizes the whole Western scholars have an ulterior motive for destroying Islam and al-Qur’ān. Basically, the research findings state that Western non-Muslim scholars are very diverse, and sometimes even contradictory. Thus, Muslim scholars are expected to participate in enriching Qur’ānic studies by supporting or refuting their findings, or providing new findings